Minimal synthetic cells to study integrin-mediated adhesion - Frohnmayer, Johannes; Böhm, Heike; Spatz, Joachim P. (Angewandte Chemie. International edition, 2015)
To shed light on cell-adhesion-related molecular pathways, synthetic cells offer the unique advantage of a well-controlled model system with reduced molecular complexity. Herein, we show that liposomes with the reconstituted platelet integrin αIIbβ3 as the adhesion-mediating transmembrane protein are a functional minimal cell model for studying cellular adhesion mechanisms in a defined environment. The interaction of these synthetic cells with various extracellular matrix proteins was analyzed using a quartz crystal microbalance with dissipation monitoring. The data indicated that integrin was functionally incorporated into the lipid vesicles, thus enabling integrin-specific adhesion of the engineered liposomes to fibrinogen- and fibronectin-functionalized surfaces. Then, we were able to initiate the detachment of integrin liposomes from these surfaces in the presence of the peptide GRGDSP, a process that is even faster with our newly synthesized peptide mimetic SN529, which specifically inhibits the integrin αIIbβ3.
Gesehen am 05.08.2021